Training of Fish Nugget Processing to Prevent Stunting - Rismaya, Rina; Sulistyawati, Eko Yuliastuti Endah; Ratnaningsih, Dewi Juliah; Maulida, Iffana Dani; Nadia, Lula (Universitas Padjadjaran, 2024)
Insufficient protein intake in children during the growth period is one of the causes of the increasing prevalence of stunting children in Indonesia. Fish has been researched to contain high levels of protein which is good for children's growth and development. In general, fish is only processed simply so it is not liked by children, whereas it can be processed into various processed products, such as nuggets. This community service aimed to determine the effect of providing fish nugget processing training on the knowledge of training participants. An increase in knowledge was measured using a one group pretest posttest design, which was then carried out with a real difference test to see the difference in the average pretest and posttest scores using the non-parametric Wilcoxon test. This training activity was given to 16 housewives and parents of Early Childhood Education School students in Situ Udik Village, Cibungbulang District, Bogor Regency with age characteristics ranging from 20-60 years and the latest education level was Elementary School-Senior High School. The results of this community service showed that providing training has a significant effect on increasing the knowledge of training participants in processing fish nuggets. The average pretest score of training participants (74.38%) showed a value that is significantly different from the average posttest score (95.63%) with significance value (Asymp. Sig.) 0.000. It is hoped that the results of this community service can be implemented by the community in producing fish-based nuggets for family consumption and sale to consumers.Keywords: Fish nuggets, food processing training, processed fish products, Situ Udik village, stunting.